2003
DOI: 10.2139/ssrn.371101
|View full text |Cite
|
Sign up to set email alerts
|

Financial Policies and the Aggregate Productivity of the Capital Stock: Evidence from Developed and Developing Economies

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…Other studies have also confirmed the lack of significance of "sequencing." Arestis, Demetriades, and Fattouh [2003] survey the literature and offer their own empirical investigation, and find no evidence that varying the sequence of financial liberalization along McKinnon's [1993] optimal lines leads to any different results. In line with Weller's [2001] findings, there is strong evidence of increasing frequency and severity of financial crises in the wake of liberalization.…”
Section: Sequencing Macrostability and Political Economymentioning
confidence: 99%
“…Other studies have also confirmed the lack of significance of "sequencing." Arestis, Demetriades, and Fattouh [2003] survey the literature and offer their own empirical investigation, and find no evidence that varying the sequence of financial liberalization along McKinnon's [1993] optimal lines leads to any different results. In line with Weller's [2001] findings, there is strong evidence of increasing frequency and severity of financial crises in the wake of liberalization.…”
Section: Sequencing Macrostability and Political Economymentioning
confidence: 99%
“…Beck et al (2000) show that financial intermediaries help economic growth through more efficient resource allocation rather than through investment or saving. Arestis et al (2003) argue that financial policies affect growth mainly through total factor productivity (TFP). Rioja and Valev (2004) find that finance has a strong positive effect on productivity growth primarily in more developed economies.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also confirmed the lack of significance of 'sequencing'. Arestis et al (2003) survey the literature and, also, offer their own empirical investigation, but find no evidence that varying the sequence of financial liberalisation, along McKinnon's (1991) optimal lines, leads to any different results. In line with findings, there is strong evidence of increasing frequency and severity of financial crises in the wake of liberalisation.…”
Section: Theoretical Aspectsmentioning
confidence: 98%